KERJASAMA PEMERINTAH DAN LSM PATTIRO DALAM PROGRAM PEMELIHARAAN KESEHATAN MASYARAKAT SURAKARTA - Rina Cahyaningrum; Priyatno Harsasto; Mohammad Adnan (Journal of Politic and Government Studies, 2014)
Surakarta is one of the city that offers the policy innovation in the realm of public service that includes education sector, health and community development. PKMS is one of the programs in the form of health care which is distributed to the public in Surakarta City in the form of aid outpatient treatment and hospitalization in general hospital of Surakarta and the health center or other designated hospitals. PKMS program management related to the division of labor is basically done by the Technical Implementation Unit (UPT) PKMS under the structure of Health Agency Surakarta City in accordance with the Local Regulation of Surakarta No. 6 of 2008 on the Organization and Administration of Local Government Surakarta City and Mayor Regulation of Surakarta number 20-K for 2009.This study analyzed the cooperation between Surakarta City Government and NGOs Pattiro in Community Health program of Surakarta. The cooperation that performed is in the form involvement of NGOs Pattiro in the program Community Health Surakarta from planning, implementation and evaluation. The purpose of this study is to know the implementation, the factors that drive the success and perceived barriers in partnership.In this study, researchers used a qualitative approach that will result in descriptive data. This study was conducted in Surakarta City. Data in this study was obtained through observations, interviews with Mrs. Ida Angklaita, SKM as head UPTD PKMS Surakarta Health Agency, Supriyanto.Skom as head of the TU PKMS Surakarta Health Agency, sulatri, S.os as program staff of NGOs Pattiro Surakarta, Alif Basuki as staff Program Manager of NGOs Pattiro Surakarta, the media and the public are able to provide information, as well as the data obtained from the document.Cooperation in Surakarta City Government and NGOs Pattiro in the program PKMS in the form program feedback mechanism between government of Surakarta City and NGOs Pattiro. The partnership uses the coordinate system that is run through partnership in discussions, seminars and workshops.Keywords: Partnership, Implementation, PKMS Program